Plasma polymerization for biomedical applications: A review. Issue 11 (20th September 2022) - Coad, Bryan R.; Favia, Pietro; Vasilev, Krasimir; Griesser, Hans J.
Abstract: Plasma polymers have long been of interest as thin film coatings on biomedical devices and products, to generate desirable surface properties for favorable bio‐interfacial interactions. Plasma polymers have also been used as platforms for the covalent immobilization of bioactive molecules. More recently, additional aspects have been investigated, such as selective prevention of adhesion of microbial pathogens, either via plasma polymers per se or including antimicrobial drugs. Plasma polymers have also been investigated for the release of silver ions and small organic molecules. Complementing low‐pressure plasma approaches, processes at atmospheric pressure have attracted interest recently, including for nano/biocomposite coatings. This contribution reviews the use of plasma polymers for intended biomedical applications, with a focus on more recent topic areas. Abstract : Plasma polymers have long been of interest as thin film coatings on biomedical devices and products, to generate desirable surface properties for favorable bio‐interfacial interactions. Plasma polymers have also been used as platforms for the covalent immobilization of bioactive molecules. More recently, additional aspects have been investigated, such as selective prevention of adhesion of microbial pathogens. Complementing low‐pressure plasma approaches, processes at atmospheric pressure have attracted interest recently, including for nano/biocomposite coatings. This contribution reviews the use of plasma polymers for intended biomedical applications, with a focus on more recent topic areas.